ASMĀ' AL-A'DĀD WA KINĀYĀTUHA FĪ AL-QUR'AN AL-KARĪM (DIRĀSAH TAHLĪLIYYAH NAHWIYYAH) - Rezeka Ma'rifatul Mahmudah (UIN ANTASARI, 2020)
In the types of words there is a chapter on numerals and their kinayah. It is widely used in Arabic, either in conversation or in Arabic texts. The purpose in this research is to describe the number words and their kinayah, as well as the form of the number word phrase and the position of the number word and its kinayah in the verse of the holy Quran. The type in this research is library research with a content analysis design (adapted from Krippendorf) because it is based on the data sources in this study in the form of documents. The primary data in this study was the holy Quran and the secondary data in this study were taken from books related to the research. And the results of this study, 1. Quantity of number word 37 words in the Quran 2. Quantity of kinayah number in the Quran 4 words 3. Quantity of position number 17 verse in the Quran 4. Quantity of position kinayah number 6 verse in the Quran.